Ancillary and instrumental body movements during inhalation in clarinetists - Nusseck, Manfred; Immerz, Anna; Hohagen, Jesper; Spahn, Claudia (Frontiers in Psychology, 2024)
Background Playing a musical instrument requires physical movements that are involved in sound production and movements with more expressive and communicative characteristics. Both movements co-occur during a performance; however, the interaction between the movements is still unclear. Methods Using motion capture technology, the movement patterns of clarinetists were analyzed at certain points in a performance to investigate how instrumental and ancillary movements interplay. Movements in the arms and knees of clarinetists during a performance were recorded using this technology. The mean angular movements at specific points in the piece, where some players inhaled and others did not, were compared. Results While the players who inhaled adopted significantly more upright body and neutral arm positions, the players who did not inhale seemed less interrupted in their performance. The results showed that the players performed rather individual ancillary movements, but at specific points, such as during melodic transitions, they performed similarly. At certain points in the melody, while some players needed to inhale, others adjusted their playing according to the inhalation moment to adopt a suitable body position. Discussion The ancillary movement was consequently interrupted by the physiological necessity to inhale. The findings provide more insights into the interplay of instrumental and ancillary movements during a performance.